2003
DOI: 10.1177/0146167203256923
|View full text |Cite
|
Sign up to set email alerts
|

Social Categorization and Fear Reactions to the September 11th Terrorist Attacks

Abstract: Two experiments were run in The Netherlands and Belgium 1 week after the terrorist attacks against the World Trade Center in New York on September 11, 2001. The aim was to investigate whether social categorization affected emotional reactions, behavioral tendencies, and actual behaviors. Results showed that focusing participants' attention on an identity that included American victims into a common ingroup led them to report more fear and stronger fear-related behavioral tendencies and to engage more often in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
114
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(128 citation statements)
references
References 11 publications
(27 reference statements)
10
114
0
4
Order By: Relevance
“…This research is critically important. Dumont et al (2003) have shown for example that ingroup-outgroup social categorization can shape emotional reactions to a terrorist attack. Nevertheless, equally important are studies that examine people who are confronted with real instances of terrorism.…”
Section: Methodological Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…This research is critically important. Dumont et al (2003) have shown for example that ingroup-outgroup social categorization can shape emotional reactions to a terrorist attack. Nevertheless, equally important are studies that examine people who are confronted with real instances of terrorism.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Terrorism is a form of political violence that seeks to instill fear, anxiety and chaos (Dumont, Yzerbyt, Wigboldus & Gordijn, 2003). It can take many forms and reflect the actions of a State.…”
mentioning
confidence: 99%
“…tentang pengaruh kategorisasi identitas terhadap reaksi emosi, kecenderungan berperilaku, dan tingkah laku aktual membuktikan bahwa memberi perhatian terhadap identitas korban menyebabkan terpancingnya reaksi emosi. Dalam situasi seperti itu, emosi yang bersumber dari identifikasi kelompok muncul dan menonjol sehingga kemarahan dan kebencian terhadap pihak yang menyebabkan jatuhnya korban muncul ke permukaan (Dumont, et al 2003).…”
Section: Identitas Sosial Kelompok Jihadisunclassified
“…A dynamic interaction has been observed between emotion and ingroup/out-group boundaries in post-terrorism contexts. In a study in Belgium and the Netherlands in the week after 9/11, Dumont, Yzerbyt, Wigboldus, & Gordijn (2003) manipulated in-group CONSTRUCTION OF SELF AND OTHER AFTER TERRORISM 1 boundaries. When the victims were seen as part of the in-group, participants had higher ratings for fear and reported being more likely to engage in information-seeking and social sharing.…”
Section: Emotionsmentioning
confidence: 99%